Direct Construction of Corrole‐Peptide Conjugates by Controllable Bilane Formation on Resin. Issue 25 (22nd March 2023) - Wu, Yue; Chau, Ho‐Fai; Kai, Hei‐Yui; Tam, Wing‐Sze; Yeung, Yik‐Hoi; Thor, Waygen; Cheung, Tsz‐Lam; Xie, Chen; Zhang, Jing‐Xiang; Wong, Ka‐Leung
Abstract: Corroles have attracted increasing research interests in recent decades owing to their unique properties over porphyrins. However, the relatively inefficient and tedious synthetic procedures of corrole building blocks with functional groups for bioconjugation hindered their bioapplications. Herein, we report a highly efficient protocol to synthesize corrole‐peptide conjugates with good yields (up to 63 %) without using prepared corrole building blocks. By condensing two −COOH‐bearing‐dipyrromethane molecules onto an aldehyde group on resin‐bound peptide chains in a controllable manner, a series of desired products with long (up to 25 residues) and bioactive peptide chains were obtained with at most one chromatographic purification. The synthesized compounds exhibited potential applications as chelators for metal ions for biomedical applications, as building blocks for supramolecular materials, as well as targeted fluorescent probes. Abstract : Solid ‐phase peptide synthesis : An efficient and practical protocol is reported to functionalize peptides by corrole motifs without using prepared corrole building blocks. The synthesized corrole‐peptide conjugates displayed their multifunctionality for metal chelating, aggregation, as well as targeted imaging.